Studying of the Expression of BAX and BCL-2 Genes in Men with Sperm DNA Fragmentation Based on DFI and Comet Assay - Hossein Taheri; Mohammad Salehi; Tarlan Eslami Arshaghi; Majid Mosahebi (Negah Institute for Scientific Communication, 2015)
Introduction: The amount of expression of BAX and BCL-2 genes in infertile men's sperm as well as its association with sperm parameters and DNA fragmentation index is an issue which has not been studied yet. In this research, it is assumed that up-regulation of BAX and downregulation of BCL-2 are directly associated with sperm DNA fragmentation. Methods: After obtaining semen samples from the patients by using gradient centrifugation method, the semen samples were centrifuged using gradient method in order to obtain pure sperm. Sperm is divided into three parts based on which flow cytometry, Real Time-PCR and Comet Assay techniques were conducted. After extracting RNA and producing cDNA, the amount of expression of BAX and BCL-2 genes was measured using Real Time-PCR. The amount of sperm DNA fragmentation was measured using flow cytometry and Comet Assay techniques. Based on the amount of DNA fragmentation index (DFI), samples were divided into the two groups of control (DFI<30) and DNA fragmentation (DFI;ge30). Using WHO criteria, sperm parameters (morphology and motility) were evaluated. Results: This study showed that the amount of expression of BAX in the DNA fragmentation group was not significant compared to the control group but the expression of BCL-2 gene decreased significantly (P<0.05). Also, in many cases, there was a significant difference between the two groups in terms of parameters of sperm DNA fragmentation and morphological parameters (P<0.05). Conclusion: This study showed that reduction of expression of BCL-2 increases sperm DNA damage and this result can be helpful for therapeutic purposes.